Effective Small and Medium-Sized Enterprise Import Strategy: Its Drivers, Moderators, and Outcomes - Leonidou, Leonidas C.; Palihawadana, Dayananda; Aykol, Bilge; Christodoulides, Paul (My University, 2022)
The authors propose a conceptual model of the drivers, moderators, and outcomes of a firm's effective import strategy, anchored on the dynamic capabilities and industrial organization theories. Whereas the former theory explains the mechanism through which dynamic capabilities facilitate import strategy effectiveness, which boosts competitive advantage and ultimately enhances financial performance, the latter theory sets the foundation for explaining the contingency role of both competitive intensity and environmental uncertainty on translating effective import strategy into competitive advantage. The model was tested using a sample of 151 small and medium-sized British importers, with results indicating that high levels of certain dynamic capabilities of a generic (i.e., adaptive and entrepreneurial) and import-specific (i.e., source identification and market development) nature are conducive to import strategy effectiveness. Study results also revealed that import strategy effectiveness generates both a product-differentiation advantage and a low-cost advantage, although this is contingent on the degree of competitive intensity and environmental uncertainty prevailing in the importer's home market. Finally, the study confirmed that both productdifferentiation advantage and low-cost advantage have a favorable impact on the importer's financial performance.
Keywords: Importing; Dynamic capabilities; Competitive advantage; Financial performance; Small and medium-sized enterprises